2023
DOI: 10.3390/healthcare11040464
|View full text |Cite
|
Sign up to set email alerts
|

Types and Sources of Social Support Accessible to University Students with Disabilities in Saudi Arabia during the COVID-19 Pandemic

Abstract: University students with disabilities face an increased risk of experiencing negative implications in educational, psychological, and social spheres during the COVID-19 pandemic. This study aimed at assessing various dimensions of social support and its sources during the COVID-19 pandemic that availed university students with disabilities. This cross-sectional descriptive study collected data from 53 university students with disabilities. We administered the Social Support Scale (SSC) to assess five dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(37 reference statements)
0
0
0
1
Order By: Relevance
“…Este resultado indica que la satisfacción con la vida es influenciada por el apoyo social en su dimensión amigos y personas importantes y se encuentra en coherencia con estudios similares donde los amigos y las personas importante juegan un rol importante en el desarrollo del estudiante y por ende predicen su satisfacción con la vida (43). Otro estudio pero en población de estudiantes con discapacidad se mostró que los universitarios dependían de sus amigos especialmente en el apoyo informativo (44); así mismo, En Tailandia un estudio mostró que el apoyo de amigos es fundamental para mejorar su bienestar (45).…”
Section: Discusión Y Conclusionesunclassified
“…Este resultado indica que la satisfacción con la vida es influenciada por el apoyo social en su dimensión amigos y personas importantes y se encuentra en coherencia con estudios similares donde los amigos y las personas importante juegan un rol importante en el desarrollo del estudiante y por ende predicen su satisfacción con la vida (43). Otro estudio pero en población de estudiantes con discapacidad se mostró que los universitarios dependían de sus amigos especialmente en el apoyo informativo (44); así mismo, En Tailandia un estudio mostró que el apoyo de amigos es fundamental para mejorar su bienestar (45).…”
Section: Discusión Y Conclusionesunclassified
“…This also affects the quality of their academic life which translates into high grades, positive emotional feelings, and high self-esteem. In addition, studies revealed that disabled students depend heavily on their friends as colleagues as a source of sustainable esteem support (Bronkema and Bowman, 2019;Ahmed et al, 2023).…”
Section: Friends Support Physical Self-esteem and Qol For Disabled St...mentioning
confidence: 99%